Single Cell Imaging to Probe Mesenchymal Stem Cell N-Cadherin Mediated Signaling within Hydrogels - Vega, Sebastián L. (Ann Biomed Eng, 2016)
N-cadherin (Ncad) mediates cell-cell interactions, regulates β-catenin (βcat) signaling, and promotes the chondrogenic differentiation of mesenchymal lineage cells. Here, we utilized confocal imaging to investigate the influence of Ncad interactions on single mesenchymal stem cell (MSC) behavior within 3-dimensional hydrogel environments under conditions that promote chondrogenic differentiation. Human MSCs were photoencapsulated in hyaluronic acid (HA) hydrogels functionalized with Ncad mimetic peptides and compared to cells in environments with control non-active peptides (Ctrl). Using single-cell imaging, we observed a significant increase in membrane βcat, nuclear βcat, and cell roundness after 3 days in Ncad hydrogels compared to Ctrl hydrogels. The extent of membrane and nuclear βcat localization and MSC roundness decreased to Ctrl hydrogel levels via pre-treatment with Ncad-specific antibodies prior to encapsulation in the Ncad hydrogels, confirming the activity of the peptide. Interestingly, there was a pronounced (>80% increase) in βcat nuclear localization in two-cell clusters within the Ctrl hydrogels, which was much greater than the increase (~30%) in βcat nuclear localization in two-cell clusters within the Ncad hydrogels. In summary, we utilized fluorescent imaging to demonstrate Ncad-mediated single cell responses to developmental cues within hydrogels towards chondrogenesis.